Moringa Oleifera Dosage Clustering for Remediation Process of Batik Effluents Using Chemometric Technique - Khairuddin, Zuriati; Juahir, Hafizan; Endut, Azizah; Ismail, Azimah; Khairul Amri Kamarudin, Mohd; Ghazali, Adiana; Mokhtar, Mazlin; Ekhwan Toriman, Mohd; Sujaul Islam, Mir; Lananan, Fathurrahman; Rahman Hassan, Abdul (International Journal of Engineering and Technology, 2018)
Batik has become one of the well-known industries because of the exclusive design and colours. The wastewater produced during the Batik production could contaminate the water bodies due to the contaminants present in the effluents. The need to remove the contaminants, in turn, calls for an efficient and effective Batik wastewater treatment prior to the disposal into the environment. The present study is purposely to determine the optimum Moringa oleifera dosage during the Batik effluents treatment process. The Batik effluent was treated using different M. oleifera seed powder dosages, swirled and allowed to settle down for 24 hours. The best dosage was determined by utilizing the cluster analysis (CA) and discriminant analysis (DA) on the observation data. The CA and DA verified that 2.5g and 5.0g are the optimum dosages to reduce the contaminants in the Batik wastewater. Additionally, both optimum dosages are the least dosage by which will also reduce the cost of M. oleifera used in the Batik wastewater treatment.Â Â